Risk management international construction joint ventures - Li, Bing. (2008)
The Asian construction market is becoming more challenging and competitive in the wake of the current regional financial crisis. For construction companies to meet the challenges, they need to enlarge their financial and technical capabilities. This can be achieved through joint ventures. International Construction Joint Venture (ICJV) is one of most effective mechanisms in gaining entry into foreign construction market. Although this type of construction business alliance can avoid certain business risk, it also brings along some other uncertain factors, which could influence normal business performance.